2004
DOI: 10.1523/jneurosci.1685-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Altered Prelimbic Cortex Output during Cue-Elicited Drug Seeking

Abstract: Cocaine treatment paired with environmental cues establishes a conditioned place preference (CPP) for that environment. After expression of this preference, rats show elevated levels of immediate early genes (IEGs; e.g. c-fos) in the prelimbic cortex (PrL), basolateral amygdala complex (BLC), and nucleus accumbens core (NAcc) compared with drug-unpaired controls. These findings, together with the known connections between these regions, suggest that they function as a circuit contributing to cue-elicited cravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 58 publications
9
71
1
Order By: Relevance
“…Increased GABAergic transmission on exposure to heroin-conditioned cues is in line with our previous observation that infusion of GABA receptor agonists muscimol and baclofen in the prelimbic area enhances cue-induced reinstatement of heroin seeking (Schmidt et al, 2005). Similarly, cocaine-seeking assessed with the conditioned place preference model is accompanied by robust activation of GABAergic interneurons, as opposed to pyramidal neurons, in the prelimbic area (Miller and Marshall, 2004). In addition, mPFC GABAergic transmission appears to be critically involved in cocaine sensitization (Steketee, 2005) and reinstatement of cocaine seeking (McFarland et al, 2003;Peters et al, 2008b).…”
Section: Discussionsupporting
confidence: 89%
“…Increased GABAergic transmission on exposure to heroin-conditioned cues is in line with our previous observation that infusion of GABA receptor agonists muscimol and baclofen in the prelimbic area enhances cue-induced reinstatement of heroin seeking (Schmidt et al, 2005). Similarly, cocaine-seeking assessed with the conditioned place preference model is accompanied by robust activation of GABAergic interneurons, as opposed to pyramidal neurons, in the prelimbic area (Miller and Marshall, 2004). In addition, mPFC GABAergic transmission appears to be critically involved in cocaine sensitization (Steketee, 2005) and reinstatement of cocaine seeking (McFarland et al, 2003;Peters et al, 2008b).…”
Section: Discussionsupporting
confidence: 89%
“…These findings, and those of others (Miller and Marshall, 2004), illustrate the importance of distinguishing the population of cells that are activated. For example, adult rats exposed to cocaine-paired cues have greater immediate early gene activity in the GABAergic inhibitory neurons of the PFC, and not in CAMK-II-expressing output neurons (Miller and Marshall, 2004). Similarly elegant studies have not been done in juveniles.…”
Section: Pfc D 1 Receptor Distribution Over Developmentsupporting
confidence: 71%
“…Within the regions evaluated in the present study, previous work has shown that prenatal exposure to cocaine leads to the loss of the synaptic cartridges of the PV+ chandelier cells in the PrL region (Morrow et al, 2003), and animals subjected to cocaine-induced conditioned place preference (CPP) show a significant induction of Fos in the PrL but not the IL (Miller and Marshall, 2004). Thus, the pyramidal outflow from the PrL, which affects targets important for reward such as the nucleus accumbens and BLA (Vertes, 2004), is critical for the expression of CPP (Miller and Marshall, 2005) and possibly for sensitization to repeated AMPH administration (present results).…”
Section: Discussionmentioning
confidence: 88%